PERBEDAAN PENERAPAN MODEL PEMBELAJARAN BERBASIS MASALAH MELALUI METODE EKSPERIMEN DENGAN METODE CERAMAH TERHADAP KEAKTIFAN DAN HASIL BELAJAR PESERTA DIDIK PADA KONSEP KEMAGNETAN DI SMAN 1 SENTANI - Umar, Sulaeman (Magister Pendidikan IPA, UNCEN, 2015)
This study aims to Know (1) The application of problem-based learning model through experimental method with a lecture on the differences in the activity of learners grade XI on the concept of magnetism in SMAN 1 Sentani. (2) The application of problem-based learning model through experimental method with a lecture on the differences in learning outcomes of students of class XI IPA on the concept of magnetism in SMAN 1 Sentani (3) The application of problem-based learning model through experimental method with a lecture to an increase in the learning outcomes grade XI students to the concept of magnetism in SMAN 1 Sentani. The design used was a kind of